STRATEGY FOR WAQF PRODUCTIVITY THROUGH ALFAMART SYSTEM AT AR-RAHMAN MART - Setiawan Bin Lahuri; Dwi Karunia Arti; Andini Rachmawati; Fadhilla Sukur Indra (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The research aims to find out the strategy for increasing waqf assets at Ar-Rahman Mart. This study is qualitative research using field research methods. Data collection by interviews, observation, and documentation. The results indicate that Ar-Rahman Mart is an effort to produce waqf assets for prospering the mosque through profit motivation. Ar-Rahman Mart is a collaboration between CV Ar-Rahman and Alfamart which is based on a five-year franchise partnership. The profit sharing from this collaboration is 90% for CV Ar-Rahman and 10% for Alfamart, but this profit will be shared after all Ar-Rahman Mart operational costs have been paid. In addition, both parties have the same goal in this collaboration, namely to improve the welfare of the people. Sidee it, Alfamart has a strategy for increasing consumer spending in interest by a system, namely the product promotion strategy and the product communication strategy.